Soil texture affects the coupling of litter decomposition and soil organic matter formation. (August 2021) - Angst, Gerrit; Pokorný, Jan; Mueller, Carsten W.; Prater, Isabel; Preusser, Sebastian; Kandeler, Ellen; Meador, Travis; Straková, Petra; Hájek, Tomáš; van Buiten, Gerard; Angst, Šárka
Abstract: Incomplete knowledge on the environmental factors linking litter decomposition and the formation of soil organic matter (SOM) hampers the sustainable management of soil as a carbon (C) sink. Here, we explored the effect of soil texture on the fate of C from decomposing litter (Indiangrass; Sorghastrum nutans (L.) Nash) and the concurrent formation of SOM in mineral soils of different textures (sand- and clay-rich) and forest floor material. We quantified the amount of litter C respired, C remaining in the litter, and litter C retained in the soil/forest floor in a 186-day incubation employing stable isotope analyses ( 13 C). We complemented our isotopic approach with the extraction of microbial biomarkers from the litter and soils/forest floor material and spectroscopic studies into the compositional changes of the incubated materials. We found that soil texture affected both the decomposition of litter and the retention of litter-derived C in the soil. The soil rich in clay provided conditions favorable for a more efficient microbial utilization of the litter material (high pH and high C use efficiency) as compared to the sand-rich soil and the forest floor. This resulted in lower amounts of litter C respired as CO2 (25.0%, vs. 55.6 and 56.1% in clay vs. sand and forest floor material, respectively) and higher amounts of litter C retained in the clay-rich soil (12.6% vs. 3.5 and 5.3% in clay vs. sand and forest floor material, respectively). High contents of silt- and clay-sized mineral particles in the clay-rich soil likely resulted in the ability to stabilize litter C in aggregates and organo-mineral associations, perhaps as microbial residues. This ability was low in the sand-rich soil and virtually absent in the forest floor, where the recalcitrance of the litter and native SOM was probably more relevant, and a larger portion of litter C may have been retained in the soil as relatively untransformed plant compounds. We emphasize that litter decomposition, the formation of SOM, and soil texture are tightly linked, such that any differences in soil texture alter litter decomposition and SOM formation patterns for the same litter. Highlights: Role of clay/sand/forest floor in litter decomposition and SOM formation evaluated. Clay-rich soil retained most litter C, while litter in this soil decomposed slowest. Favorable conditions for efficient microbial use of litter C in clay-rich soil. High amount of fine particles resulted in high ability to retain new litter C. Soil texture differences affect litter decomposition & soil C sequestration rates.